Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(\left(2x+1\right)^3=5^3\)
\(\Rightarrow2x+1=5\)
\(2x=5-1\)
\(2x=4\)
\(x=4:2\)
\(x=2\)
\(b,\left(2x-1\right)^3=125\)
\(\Rightarrow2x-1=5\)
\(2x=5+1\)
\(2x=6\)
\(x=6:2=3\)
b) \(\left(2x-1\right)^3=125\)
\(\left(2x-1\right)^3=5^3\)
\(2x-1=5\)
\(2x=5+1\)
\(2x=6\)
\(x=6:2\)
\(x=3\)
(2x+1)^3=125
=> (2x + 1 )^3 = 5^3
=> 2x + 1 = 5
=> 2x = 5 - 1
=> 2x = 4
=> x = 4 : 2
=> x = 2
a) \(\left(2x-1\right)^3=27\)
\(\Rightarrow\left(2x-1\right)^3=3^3\)
\(\Rightarrow2x-1=3\)
\(\Rightarrow2x=3+1=4\)
\(\Rightarrow x=4:2=2\)
b) \(\left(2x+1\right)^3=125\)
\(\Rightarrow\left(2x+1\right)^3=5^3\)
\(\Rightarrow2x+1=5\)
\(\Rightarrow2x=5-1=4\)
\(\Rightarrow x=4:2=2\)
c) \(\left(x+2\right)^3=\left(2x\right)^3\)
\(\Rightarrow x+2=2x\)
\(\Rightarrow2=2x-2=1x\)
\(\Rightarrow x=2:1=2\)
d) \(\left(2x-1\right)^7=x^7\)
\(\Rightarrow2x-1=x\)
\(\Rightarrow-1=x-2x\)
\(\Rightarrow-1=-x\)
\(\Rightarrow x=1\)
(2x + 1 )^3 = 125
(2x + 1 )^3=5^3
\(\Leftrightarrow\)2x + 1 =5
2x = 5-1
2x = 4
x=4:2
x=2
(2x+1)^3=125
<=>2x+1=5 (vì là bậc 3 nên giữ nguyên dấu)
<=>2x=4
=>x=2
a.
(2x+1)2 = 25 = 52
=> 2x + 1 = 5
=> 2x = 4
=> x = 2
Vậy x = 2
b.
52x+1 = 125 = 53
=> 2x + 1 = 3
=> 2x = 2
=> x = 1
Vậy x = 1
Chúc em học tốt!!!
2x=125-1
2x=124
x=124:2
x=62
2x + 1 = 125
2x = 125 - 1
2 . x = 124
x = 124 : 2
x = 62